2011
DOI: 10.1071/cp11007
|View full text |Cite
|
Sign up to set email alerts
|

Yield, transpiration efficiency, and water-use variations and their interrelationships in the sorghum reference collection

Abstract: Sorghum is well adapted to water-limited conditions, but the traits responsible for this enhanced adaptation under drought conditions remain unclear. In this study, yield, transpiration efficiency (TE) and water extraction were assessed in 149 germplasm entries from the sorghum reference set (plus three control cultivars) using a lysimetric system under terminal water stress and fully irrigated conditions outdoors. A 10-fold range for grain yield and harvest index (HI), 2-fold range for TE and a 1.25-fold vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 35 publications
(1 reference statement)
8
85
3
Order By: Relevance
“…Importantly, genotypes that extract more water during the grain filling period extract less water during the vegetative stage (e.g. Vadez et al 2011bVadez et al , 2013aZaman-Allah et al 2011a). The continued extraction of water at later stages therefore appears to depend on water-saving mechanisms functioning at earlier stages, and water extraction by the root at key stages is a dynamic process that does not depend only on the root tapping more water at depth.…”
Section: The Need For Dynamic Measurements Of Water Extraction At Keymentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, genotypes that extract more water during the grain filling period extract less water during the vegetative stage (e.g. Vadez et al 2011bVadez et al , 2013aZaman-Allah et al 2011a). The continued extraction of water at later stages therefore appears to depend on water-saving mechanisms functioning at earlier stages, and water extraction by the root at key stages is a dynamic process that does not depend only on the root tapping more water at depth.…”
Section: The Need For Dynamic Measurements Of Water Extraction At Keymentioning
confidence: 99%
“…Therefore, to understand these complex interactions, methods are needed that can be used to analyse as many components as possible related to plant water balance such that a comprehensive understanding can be achieved. Recently, a lysimetric system has been developed , in which plant water use can be monitored from a very early growth stage until maturity and highly relevant agronomic assessments can be performed in conditions that mimic field situations at least in terms of plant density and the soil and water volume available to each plant (Ratnakumar and Vadez 2011;Vadez et al 2011aVadez et al , 2011bVadez et al , 2013bZaman-Allah et al 2011a). In particular, this system allows the measurement of water extraction at key stages, especially the grain filling period, and it can be used to assess leaf conductance using the index of stomatal conductance (Zaman-Allah et al 2011a).…”
Section: What Progress Is Needed In 'Water Stress' Research?mentioning
confidence: 99%
“…The novelty of the approach is also in allowing to obtain highly relevant agronomic data in a system where the homogeneity of the soil can be controlled, whereas studies in low soil P field are often bound to face large field heterogeneity in P availability. Such a system has recently been used to assess water use throughout the cropping cycle until maturity in different crops (Ratnakumar and Vadez 2011;Vadez et al 2011a;Zaman-Allah et al 2011). It has also been tested to produce highly relevant agronomic data in low and high P soils (Karanam and Vadez 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been tested to produce highly relevant agronomic data in low and high P soils (Karanam and Vadez 2010). The setup allows to determine transpiration efficiency (TE, calculated as dry matter (DM) produced per kg of water transpired) to distinguish tolerant and sensitive genotypes (Ratnakumar and Vadez 2011;Vadez et al 2011a;. It is well known that TE depends on interactions between water and nutrient availability (De Wit 1958;Tanner and Sinclair 1983;Clarkson et al 2000;Vadez et al 2014), and is particularly affected by nutrient deficiency (Payne 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Condon et al (1990) reported a significant (P<0.01) positive correlation between TE in well watered and drought stressed conditions. Although significant G×E interactions for TE have been observed in both sorghum (Xin et al, 2009;Vadez et al, 2011b) and peanut (Krishnamurthy et al, 2007), the G×E effect was smaller than the genotypic main effect in each of these studies. All available evidence thus suggests that G×E interactions for TE are likely to be minor relative to the genotypic main effects.…”
Section: Discussionmentioning
confidence: 89%